Amphiphilic Oxo-Bridged Ruthenium “Green Dimer” for Water Oxidation - Yang, Qing-Qing; Jiang, Xin; Yang, Bing; Wang, Yang; Tung, Chen-Ho; Wu, Li-Zhu (iScience, 2020)
In 1982, an oxo-bridged dinuclear ruthenium(III) complex, known as “blue dimer,” was discovered to be active for water oxidation. In this work, a new amphiphilic ruthenium “green dimer” 2, obtained from an amphiphilic mononuclear Ru(bda) (N-OTEG) (L1) (1; N-OTEG = 4-(2-(2-(2-methoxyethoxy)ethoxy)ethoxy)-pyridine; L1 = vinylpyridine) is reported. An array of mechanistic studies identifies “green dimer” 2 as a mixed valence of RuII-O-RuIII oxo-bridged structure. Bearing the same bda2- and amphiphilic axial ligands, monomer 1 and green dimer 2 can be reversibly converted by ascorbic acid and oxygen, respectively, in aqueous solution. More importantly, the oxo-bridged “green dimer” 2 was found to take water nucleophilic attack for oxygen evolution, in contrast to monomer 1 via radical coupling pathway for O-O bond formation. This is the first report of an amphiphilic oxo-bridged catalyst, which possesses a new oxygen evolution pathway of Ru-bda catalysts. [Display omitted] •Green dimer (RuII-O-RuIII), referring to “blue dimer” of RuIII-O-RuIII, is disclosed•The first amphiphilic μ-oxido-bridged catalyst is reported active for water oxidation•The oxo-bridged “green dimer” 2 takes water nucleophilic attack for O-O bond formation•This is the first Ru-bda catalyst, which possesses a new oxygen evolution pathway Inorganic Chemistry; Catalysis; Materials Chemistry